Irish-Newfoundland Step Dancing and Cultural Identity in Newfoundland - Walsh, Kristin (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
AbstractStep dancing in Newfoundland and Labrador has endured a significant contextual shift in order to remain relevant as both cultural piece and performance genre and it continues to evolve in context and function today, while adhering to Newfoundland’s collective identity. Through its examination of the St. Pat’s Dancers, a St. John’s-based children’s step dancing group, this article addresses the larger philosophical questions of authenticity, heritage and revival in vernacular dance. As a case study in Newfoundland vernacular dance, the St. Pat’s Dancers links together notions of heritage promotion and preservation, and the commodification of culture through the lens of Irishness that is prevalent in Newfoundland culture.